(Emotional intelligence and Their Relationship with Psychological Immunity for Preparatory Students ) (Journal of the College of Basic Education, 2022)
The current research aims to identify :-The degree of Emotional intelligence among the students of Preparatory StudentsThe degree of Psychological Immunity among the students of Preparatory StudentsThe correlation between Emotional intelligence and Psychological ImmunityThe difference in relationship Emotional intelligence and the Psychological Immunity among the students of Preparatory Students according to sex variable(male-famale). To achieve the objectives of the research, which the researcher ever built scale Emotional intelligence and consists of (28) items and four alternatives to measure the Emotional intelligence . and ever built the scale Psychological Immunity consisting of (26)items and four alternatives to measure the Psychological Immunity. After applying the two scales to the research sample consisting of (200 students)from Preparatory Students, the results showed that the degree of Emotional intelligence among Preparatory Students was (high) and the degree of Psychological Immunity was also (high). As for the relationship between the two variables, it is a (strong positive) relationship. The results showed no significant statistical differences between the two variables according to variable of sex.